A montmorillonite-based biomimetic bone repair composite material, a preparation method and applications thereof

CN122912175APending Publication Date: 2026-10-16CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611119762.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0037] This invention utilizes a self-assembled ion diffusion layer of montmorillonite and gelatin as a dedicated channel for directional ion diffusion, enabling ions to migrate directionally from the ion storage layer to the bone wound surface, providing an ion flow basis for electrical signal generation. The ion storage layer consists of channels formed by freeze-drying a sodium alginate-polyvinyl alcohol-montmorillonite self-assembled system and loaded divalent metal ions. Its high porosity and three-dimensional channel structure not only allow for the controlled release of ions from the raw materials' ion adsorption properties, maintaining a long-term stable concentration gradient and ensuring the continuity of the electrical signal, but also adsorb and store a large number of metal ions, resulting in an ion concentration far exceeding the ion concentration level of the physiological fluid at the bone wound surface. This, in turn, creates a stable ion concentration gradient between the bone repair composite material and the bone wound surface. The encapsulation layer completely covers the integrated biphasic structure (leaving only the ion diffusion layer facing the bone wound surface to release divalent metal ions), preventing non-directional ion leakage, avoiding concentration gradient disturbances, and ensuring the stability of directional ion diffusion and the consistency of electrical signal output. The ion diffusion layer, ion storage and release layer, and encapsulation layer work together to construct a self-generated, continuously stable electrical signal generation system that does not require external force. This system can adapt to different bone biomechanical environments and has good biocompatibility and no cytotoxicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912175A_ABST
    Figure CN122912175A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of bone repair materials, and particularly relates to a biomimetic bone repair composite material based on montmorillonite, a preparation method and application thereof. The biomimetic bone repair composite material based on montmorillonite is composed of an ion diffusion layer, an ion storage and release layer and an encapsulation layer in sequence, the ion diffusion layer and the ion storage and release layer have the same planar shape, and the two layers are tightly attached to form an integrated two-phase structure, the encapsulation layer entirely covers the integrated two-phase structure, and the surface of the ion diffusion layer away from the ion storage and release layer is not covered; the ion diffusion layer is prepared by self-assembly of montmorillonite and gelatin in water and vacuum filtration molding; the ion storage and release layer is prepared by self-assembly of sodium alginate, polyvinyl alcohol and montmorillonite in water, freeze-drying to form a pore aerogel, and then loading divalent metal ions through cross-linking; the encapsulation layer is prepared by solidification of poly(D, L-lactic acid-co-glycolic acid) solution; and the planar area ratio of the ion diffusion layer and the ion storage and release layer is 1.5-2.5:1. 2+ cross-linking, and loading of divalent metal ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of bone repair materials technology, specifically relating to a biomimetic bone repair composite material based on montmorillonite, its preparation method, and its application. Background Technology

[0002] Bone defect repair is a major concern in the medical field, as bone defects can lead to severe pain and inflammation, thus impacting patients' quality of life. There are many causes of bone defects, such as trauma, tumors, infections, and congenital malformations. Currently, there are various methods for treating bone defects, including bone grafting, artificial bone, and bioactive materials; however, these methods all have certain limitations and potential complications.

[0003] The extracellular matrix of bone cells is assembled from hydroxyapatite nanocrystals distributed along collagen fibers. Collagen and hydroxyapatite form semiconductive junctions, thus bone tissue contains natural electroactive functional units. Furthermore, endogenous "electricity" plays a crucial role in regulating osteogenic differentiation, proliferation, and gene expression of stem cells; therefore, electrical stimulation can promote bone tissue regeneration. The piezoelectric effect is a physical phenomenon where, under mechanical stress (such as pressure, vibration, or tension), the positive and negative charge centers within certain materials undergo relative displacement, generating spontaneous polarization and accumulating equal amounts of oppositely charged bound charges on the material surface, forming a potential difference. Bone repair piezoelectric materials are a class of functional materials that rely on the piezoelectric effect to achieve direct conversion of mechanical energy to electrical energy. They can harvest mechanical energy from human movement and physiological mechanical loads and convert it into biocompatible electrical signals, thereby enhancing the bone tissue formation process, simulating and regulating the physiological electrical microenvironment of bone defect areas, and providing electrostimulation-regulated support for bone regeneration. For example, patent CN104208754B discloses a piezoelectric active bone repair composite material and its preparation method. The composite material is composed of ceramic particle fillers with a core-shell structure and a polymer matrix. The ceramic particle fillers with the core-shell structure are uniformly dispersed in the polymer matrix. The core of the ceramic particle fillers with the core-shell structure is a ceramic particle, and the surface of the ceramic particle is coated with an organic coating layer. Patent CN116942922B discloses a hydrogel that promotes cartilage repair using the piezoelectric effect, its preparation method, and its application. The hydrogel matrix includes a biodegradable three-dimensional piezoelectric hydrogel prepared from sodium potassium niobate, polyvinyl alcohol, and polyacrylic acid. Patent CN116328043B discloses a 3D-printed piezoelectric bone repair scaffold based on shape memory polymer and its preparation method, comprising the following steps: adding barium titanate to a dopamine hydrochloride solution, stirring, adding a silane coupling agent, and after the reaction is complete, adding barium titanate to a silver ammonia solution to prepare modified barium titanate nanoparticles; adding the modified barium titanate nanoparticles to epoxidized soybean oil acrylate, adding a diluent and a photoinitiator to obtain a photocurable slurry; and using a photocurable 3D printer to prepare a bone repair scaffold with piezoelectric effect and shape memory function.

[0004] The above are common piezoelectric materials with bone repair function. However, the generation of electrical signals and electrical stimulation depends entirely on external force (such as walking and chewing) deformation, which makes it difficult to establish the early, continuous and stable electrical microenvironment that is crucial for bone repair. For example, a treatment window may be formed during the postoperative quiescent period. Moreover, the mechanical environment of bones in different parts (such as the weight-bearing femur and the non-weight-bearing jawbone) is very different, which leads to different repair effects of the same material in different parts.

[0005] Therefore, developing a novel piezoelectric material for bone repair that can autonomously generate continuous and stable electrical signals without relying on external forces and is adapted to different skeletal biomechanical environments is key to improving the clinical efficacy of bone repair. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a biomimetic bone repair composite material based on montmorillonite, its preparation method, and its applications. This invention utilizes a self-assembled ion diffusion layer of montmorillonite and gelatin as a dedicated channel for directional ion diffusion, enabling ions to migrate directionally from the ion storage layer to the bone wound surface, providing an ion flow basis for electrical signal generation. The ion storage layer consists of a three-dimensional porous structure of sodium alginate-polyvinyl alcohol-montmorillonite freeze-dried and loaded with divalent metal ions. Its high porosity and three-dimensional porous structure not only allow for the controllable release of ions due to the ion adsorption characteristics of the raw materials, maintaining a long-term stable concentration gradient and ensuring the continuity of the electrical signal, but also adsorb and store a large number of metal ions, making their ion concentration much higher than the ion concentration level of the physiological fluid at the bone wound surface, thereby forming a stable ion concentration gradient between the bone repair composite material and the bone wound surface. The encapsulation layer completely covers the integrated biphasic structure (leaving only the ion diffusion layer facing the bone wound surface), preventing non-directional ion leakage, avoiding concentration gradient disturbances, and ensuring the stability of directional ion diffusion and the consistency of electrical signal output. An ion diffusion layer, a three-dimensional ion storage and release layer, and an encapsulation layer work together to construct a self-generated, continuously stable electrical signal generation system that does not require external force. This system can adapt to different bone biomechanical environments and has good biocompatibility and no cytotoxicity.

[0007] To achieve the above objectives, the following technical solution is adopted:

[0008] A biomimetic bone repair composite material based on montmorillonite is composed of an ion diffusion layer, an ion storage and release layer, and an encapsulation layer. The ion diffusion layer and the ion storage and release layer have the same planar shape and are tightly bonded together to form an integrated biphase structure. The encapsulation layer completely covers the integrated biphase structure, leaving only the surface of the ion diffusion layer away from the ion storage and release layer unencapsulated. The ion diffusion layer is prepared by self-assembly of montmorillonite and gelatin in water followed by vacuum filtration. The ion storage and release layer is prepared by self-assembly of sodium alginate, polyvinyl alcohol, and montmorillonite in water followed by freeze-drying to form a porous aerogel, which is then subjected to Ca... 2+The encapsulation layer is prepared by cross-linking and loading divalent metal ions; the encapsulation layer is prepared by curing poly(D,L-lactic acid-co-glycolic acid) solution; the planar area ratio of the ion diffusion layer and the ion storage and release layer is 1.5-2.5:1.

[0009] The planar area ratio of the ion diffusion layer to the ion storage and release layer is 1.5-2:1. The thickness of the ion diffusion layer is 0.02-0.1 mm, preferably 0.08-0.1 mm; the thickness of the ion storage and release layer is 2-5 mm, preferably 2-3 mm. The thickness of the encapsulation layer is 0.1-0.3 mm.

[0010] The divalent metal ion is selected from at least one of calcium ions and magnesium ions.

[0011] The self-assembly conditions are as follows: ultrasonic treatment followed by stirring. Further, the ultrasonic treatment power is 200-500W, the frequency is 20-40kHz, and the time is 10-30min. The stirring speed is 400-800 rpm, and the time is 12-24h.

[0012] The montmorillonite is added in the form of a montmorillonite suspension, and the gelatin is added in the form of a gelatin solution. The solid content of the montmorillonite suspension is 1-2 wt%. The concentration of the gelatin solution is 1-2 wt%. The volume ratio of the montmorillonite suspension to the gelatin solution is 1-1.5:1.

[0013] The montmorillonite is sodium-based montmorillonite with an average particle size of 10-70 µm and an ion exchange capacity of 90-145 meq / 100g. The gelatin has a glue strength of 200-300 g Bloom.

[0014] The montmorillonite suspension is prepared by adding montmorillonite to water and then ultrasonically stirring. The ultrasonic stirring is performed with an ultrasonic power of 200-500W and a frequency of 20-40kHz, while stirring at a speed of 400-800rpm for 5-10 hours.

[0015] The gelatin solution is prepared by adding gelatin to water and heating and stirring. The temperature is raised to 60-80°C, and the stirring is carried out at a speed of 400-800 rpm for 10-30 minutes.

[0016] Sodium alginate is added in the form of a sodium alginate solution, polyvinyl alcohol is added in the form of a polyvinyl alcohol solution, and montmorillonite is added in the form of a montmorillonite suspension. The concentration of the sodium alginate solution is 1-3%, the concentration of the polyvinyl alcohol solution is 2-4 wt%, and the solid content of the montmorillonite suspension is 1-2 wt%, with a volume ratio of 0.5-1.5:0.5-1.5:0.5-1.5.

[0017] The sodium alginate has a viscosity of 100-400 mPa·s. The polyvinyl alcohol has a weight-average molecular weight of 80,000-120,000. The montmorillonite is the same as above.

[0018] The sodium alginate solution is prepared by adding sodium alginate to water and heating and stirring. The temperature is raised to 60-80°C, and the stirring is carried out at a speed of 400-800 rpm for 10-30 minutes.

[0019] The polyvinyl alcohol solution is prepared by dissolving polyvinyl alcohol in water and stirring. The stirring is carried out at a speed of 400-800 rpm for 5-10 minutes.

[0020] The method for preparing the montmorillonite suspension is the same as above.

[0021] The concentration of the poly(D,L-lactic acid-co-glycolic acid) solution is 3-6 wt%.

[0022] The poly(D,L-lactic acid-co-glycolic acid) solution contains poly(D,L-lactic acid-co-glycolic acid) with a weight-average molecular weight of 20,000-60,000, and the molar ratio of lactide to glycolide is 50-85:15-50.

[0023] The solvent in the poly(D,L-lactic acid-co-glycolic acid) solution is selected from one or more combinations of ethyl acetate, acetone, and dioxane.

[0024] The curing conditions are 20-40℃ and a vacuum of 0.03-0.05MPa for 10-30 minutes. After curing, the encapsulation layer forms a continuous and elastic sealing layer, which prevents ion leakage.

[0025] The shape of the plane is not particularly limited; it can be circular, quadrilateral, pentagonal, hexagonal, etc., depending on the different bone repair locations.

[0026] Montmorillonite is a 2:1 type layered silicate, and its crystal structure contains isomorphic substitutions (such as Al) 3+ Replacement of Si 4+The montmorillonite sheets are given an irreversible, permanent negative charge. When an external cation concentration gradient such as calcium or magnesium exists, the permanent negative charge drives the target cations to migrate directionally along the concentration gradient through electrostatic interactions. Simultaneously, equivalent substitution of exchangeable cations between layers is achieved, ensuring the continuity of ion transport. Gelatin, a natural hydrophilic polymer, binds to the montmorillonite sheets through hydrogen bonds and electrostatic interactions, forming an ordered and continuous ion conduction channel. Furthermore, its hydrophilicity ensures a tight fit between the ion diffusion layer, the ion storage layer, and the bone wound surface, preventing ion transport obstruction caused by interfacial gaps. The self-assembled ion diffusion layer prepared from montmorillonite and gelatin serves as a dedicated channel for directional ion diffusion, enabling ions to migrate directionally from the ion storage layer to the bone wound surface, providing the basis for ion flow generation of electrical signals.

[0027] The ion storage and release layer consists of channels formed by freeze-drying a sodium alginate-polyvinyl alcohol-montmorillonite self-assembled system and loaded divalent metal ions. Its high porosity and channel structure not only enable the controlled release of ions from the raw materials through ion adsorption, continuously replenishing diffused ions and maintaining a long-term stable concentration gradient, thus ensuring the continuity of the electrical signal, but also adsorb and store a large number of metal ions, making their ion concentration far higher than the ion concentration level of the physiological fluid at the bone wound surface. This, in turn, forms a stable ion concentration gradient between the bone repair composite material and the bone wound surface. By controlling the relative thickness of the ion diffusion layer and the ion storage and release layer, the ion diffusion rate can be adjusted, avoiding electrical signal fluctuations caused by rapid ion loss and ensuring the stability of the electrical signal. The encapsulation layer completely covers the integrated biphase structure (leaving only the ion diffusion layer facing the bone wound surface to release dimethyl metal ions), preventing non-directional ion leakage, avoiding concentration gradient disturbances, and ensuring the stability of directional ion diffusion and the consistency of the electrical signal output. The ion diffusion layer, ion storage and release layer, and encapsulation layer work together to construct a self-generated, continuously stable electrical signal generation system that does not require external force. This system can adapt to different bone biomechanical environments and has good biocompatibility and no cytotoxicity.

[0028] This invention also provides a method for preparing the above-mentioned montmorillonite-based biomimetic bone repair composite material, comprising the following steps:

[0029] S1 ion diffusion layer: Montmorillonite, gelatin and water are mixed to form a liquid phase, which is then self-assembled, vacuum filtered and dried for later use;

[0030] S2 ion storage and release layer: Sodium alginate, polyvinyl alcohol, montmorillonite, and water are mixed to form a liquid phase for self-assembly, poured into a mold, and freeze-dried to obtain an aerogel. Ca 2+ Cross-linked and loaded with divalent metal ions, ready for use;

[0031] S3 Bionic Bone Repair Composite Material Based on Montmorillonite: An ion diffusion layer is laid flat on a planar glass surface, an ion storage and release layer is laid flat on the surface of the ion diffusion layer to form an integrated biphase structure, a poly(D,L-lactic acid-co-glycolic acid) solution is applied, and then cured.

[0032] In step S1, the vacuum filtration is performed at a vacuum level of 0.05-0.09 MPa for 1-3 hours. The filter membrane used in the vacuum filtration has a pore size of 0.1-0.65 μm and is selected from one or more of ceramic membranes, glass membranes, polytetrafluoroethylene membranes, and mixed cellulose membranes. The drying is performed at 20-30°C and 40-60% humidity for 0.5-2 hours.

[0033] In step S2, the freeze-drying involves pre-freezing at -50 to -10°C for 0.5-6 hours, followed by freeze-drying at -45 to 40°C and a pressure of 20-40 Pa for 6-48 hours. The Ca... 2+ Crosslinking involves immersing the freeze-dried aerogel in Ca... 2+ The ion-crosslinked aerogel was obtained by filtration, separation, and washing in an aqueous solution. The soaking time was 3-6 minutes. The Ca... 2+ Ca in aqueous solution 2+ The concentration is 30-50 mmol / L, using low concentrations of Ca 2+ Aqueous solutions can be used to crosslink aerogels, resulting in mild crosslinking and a controllable crosslinking rate, avoiding the use of high-concentration Ca. 2+ The rapid over-crosslinking of the aerogel surface caused by aqueous solution forms a dense, hard shell, ensuring the Ca... 2+ Uniformly penetrates into the internal pores of the aerogel, achieving overall uniform cross-linking. The aerogel, Ca... 2+ The aqueous solution has a mass-to-volume ratio of 1g:5-10mL. The loaded divalent metal ions are obtained by impregnating the cross-linked ionic aerogel in an ionic aqueous solution, followed by filtration and removal of surface moisture with filter paper. The impregnation time is 8-24 hours. The Ca... 2+ The mass-to-volume ratio of the cross-linked ionic aerogel to the ionic aqueous solution is 1 g: 5-10 mL. The concentration of the ionic aqueous solution is 100-200 mmol / L, and it is selected from one or a combination of two of calcium chloride aqueous solution and magnesium chloride aqueous solution.

[0034] In step S3, the geometric centers of the ion diffusion layer and the ion storage layer coincide. The poly(D,L-lactic acid-co-glycolic acid) solution is prepared by adding poly(D,L-lactic acid-co-glycolic acid) to a solvent and stirring until completely dissolved. The side of the ion diffusion layer away from the ion storage layer is not coated with the poly(D,L-lactic acid-co-glycolic acid) solution. The coating is applied 1-5 times, with a time interval of 5-20 minutes between adjacent coatings.

[0035] An application of a biphasic biomimetic bone repair composite material based on montmorillonite can be used as a dental repair material and a craniofacial bone repair material.

[0036] Compared with the prior art, the beneficial effects of the present invention are:

[0037] This invention utilizes a self-assembled ion diffusion layer of montmorillonite and gelatin as a dedicated channel for directional ion diffusion, enabling ions to migrate directionally from the ion storage layer to the bone wound surface, providing an ion flow basis for electrical signal generation. The ion storage layer consists of channels formed by freeze-drying a sodium alginate-polyvinyl alcohol-montmorillonite self-assembled system and loaded divalent metal ions. Its high porosity and three-dimensional channel structure not only allow for the controlled release of ions from the raw materials' ion adsorption properties, maintaining a long-term stable concentration gradient and ensuring the continuity of the electrical signal, but also adsorb and store a large number of metal ions, resulting in an ion concentration far exceeding the ion concentration level of the physiological fluid at the bone wound surface. This, in turn, creates a stable ion concentration gradient between the bone repair composite material and the bone wound surface. The encapsulation layer completely covers the integrated biphasic structure (leaving only the ion diffusion layer facing the bone wound surface to release divalent metal ions), preventing non-directional ion leakage, avoiding concentration gradient disturbances, and ensuring the stability of directional ion diffusion and the consistency of electrical signal output. The ion diffusion layer, ion storage and release layer, and encapsulation layer work together to construct a self-generated, continuously stable electrical signal generation system that does not require external force. This system can adapt to different bone biomechanical environments and has good biocompatibility and no cytotoxicity. Attached Figure Description

[0038] Figure 1 The image shows the ion diffusion layer scanning electron microscope (SEM) morphology of the montmorillonite-based biomimetic bone repair composite material prepared in Example 1.

[0039] Figure 2 The image shows the ion reservoir layer morphology (SEM) of the montmorillonite-based biomimetic bone repair composite material prepared in Example 1.

[0040] Figure 3 The ion current-time curve is a test result of the electrical properties of the montmorillonite-based biomimetic bone repair composite material prepared in Example 1.

[0041] Figure 4 The ion concentration-time curve of the montmorillonite-based biomimetic bone repair composite material prepared in Example 1 is obtained by ICP-MS testing.

[0042] Figure 5 Photographs showing the appearance of the montmorillonite-based biomimetic bone repair composite material prepared in Example 1. Detailed Implementation

[0043] The present invention will be further described below with reference to specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, all "parts" mentioned in the embodiments of the present invention are parts by weight. All reagents used are commercially available in the art.

[0044] Polyvinyl alcohol grade A040923, weight average molecular weight 82,000, from Anaiji.

[0045] Polyvinyl alcohol grade A040928, weight average molecular weight 115,000, from Anaiji.

[0046] Sodium alginate, grade E082519, with a viscosity of 110 mPa·s, is from Anaiji.

[0047] Sodium alginate, grade E082520, with a viscosity of 400 mPa·s, is from Anaiji.

[0048] Sodium-based montmorillonite PGW has an average particle size of 16µm and an ion exchange capacity of 145meq / 100g, and is sourced from Shanghai Jiyi Biotechnology Co., Ltd.

[0049] Sodium-based montmorillonite #1 has an average particle size of 56µm and an ion exchange capacity of 92meq / 100g, and is sourced from Wengjiang Reagent.

[0050] Poly(D,L-lactic acid-co-glycolic acid) P875223 has a weight-average molecular weight of 24,000 and a lactide to glycolide molar ratio of 50:50. It is sourced from Shanghai Maclean Biochemical Technology Co., Ltd.

[0051] Poly(D,L-lactic acid-co-glycolic acid) P875234 has a weight-average molecular weight of 60,000 and a lactide to glycolide molar ratio of 65:35. It is sourced from Shanghai Maclean Biochemical Technology Co., Ltd.

[0052] Polylactic acid P729201, with a weight-average molecular weight of 60,000, is from Shanghai Maclean Biochemical Technology Co., Ltd.

[0053] Gelatin E080142 is derived from cowhide, has a glue strength of 300gBloom, and is from Shanghai Maclean Biochemical Technology Co., Ltd.

[0054] Gelatin E082450 is derived from cowhide, has a glue strength of 250gBloom, and is produced by Shanghai Maclean Biochemical Technology Co., Ltd.

[0055] Example 1

[0056] 1) A montmorillonite suspension with a solid content of 2wt% was obtained by adding 2kg of sodium montmorillonite PGW to 98kg of water, sonicating at 500W and 40kHz, and stirring at 400rpm for 5h. A montmorillonite suspension with a solid content of 1wt% was obtained by adding 1kg of sodium montmorillonite PGW to 99kg of water, sonicating at 500W and 40kHz, and stirring at 400rpm for 5h.

[0057] 2) Add 2 kg of gelatin E080142 to 98 kg of water and heat to 60°C. Stir at 800 rpm for 20 min to obtain a gelatin solution with a concentration of 2 wt%.

[0058] 3) A montmorillonite suspension with a solid content of 2wt% and a gelatin solution with a concentration of 2wt% were mixed at a volume ratio of 1:1. The mixture was stirred at 400 rpm for 24 hours with a power of 200W, a frequency of 40kHz, an ultrasonic time of 30 minutes, and a power of 400 rpm to obtain a homogeneous mixture. 10 mL of the mixture was vacuum filtered for 1 hour under a vacuum of 0.08 MPa using a WHATMAN nitrocellulose membrane with a pore size of 0.2 μm (purchased from Shanghai Jinpan Biotechnology Co., Ltd.). The filtration was carried out using a 40 mm diameter sand filter. The WHATMAN nitrocellulose membrane was peeled off, and the resulting circular filter cake was dried at 30℃ and 40% humidity for 2 hours. The cake was then molded using a stainless steel cylindrical mold with an outer diameter of 24 mm and an inner diameter of 22 mm coated with dimethyl silicone oil release agent to obtain a circular shape with a planar area of ​​121π mm². 2 An ion diffusion layer with a thickness of 0.08 mm.

[0059] 4) Add 1 kg of sodium alginate E082519 to 99 kg of water and heat to 60°C. Stir at 400 rpm for 15 min to obtain a sodium alginate solution with a concentration of 1 wt%. Dissolve 2 kg of polyvinyl alcohol A040928 in 98 kg of water and stir at 400 rpm for 5 min to obtain a polyvinyl alcohol solution with a concentration of 2 wt%.

[0060] 5) A 1 wt% sodium alginate solution, a 2 wt% polyvinyl alcohol solution, and a 1 wt% montmorillonite suspension were mixed in a volume ratio of 1:1:1. The mixture was ultrasonically treated for 30 min at 200 W and 40 kHz, and stirred for 12 h at 800 rpm. 6 mL of the resulting mixture was poured into a 15.6 mm diameter mold and pre-frozen at -45℃ for 2 h, followed by freeze-drying at -20℃ and 20 Pa for 24 h to obtain an aerogel. The freeze-dried aerogel was then immersed in a 50 mmol / L calcium chloride aqueous solution at a mass-to-volume ratio of 1 g:10 mL for 5 min, filtered, and washed once with water to obtain an ion-crosslinked aerogel. The ion-crosslinked aerogel was then immersed in a 200 mmol / L magnesium chloride aqueous solution at a mass-to-volume ratio of 1 g:10 mL for 12 h, filtered, and the surface moisture was absorbed with filter paper to obtain a circular aerogel with a planar area of ​​60.5 mm². 2 An ion storage and release layer with a thickness of 3 mm.

[0061] 6) Add 6 kg of poly(D,L-lactic acid-co-glycolic acid) P875234 to 94 kg of ethyl acetate and stir at 500 rpm for 30 min until completely dissolved to obtain a poly(D,L-lactic acid-co-glycolic acid) solution with a concentration of 6 wt%.

[0062] 7) The ion diffusion layer is laid flat on the surface of the glass, and the ion storage and release layer is laid flat on the surface of the ion diffusion layer so that the geometric centers of the two coincide. A 6wt% poly(D,L-lactic acid-co-glycolic acid) solution is applied three times, with a time interval of 10 min between two consecutive applications. Then, it is placed at 25℃ and a vacuum degree of 0.03MPa for 30 min to cure, resulting in a montmorillonite-based biomimetic bone repair composite material with an encapsulation layer thickness of 0.3 mm.

[0063] Example 2

[0064] The rest is the same as in Example 1, except that in step 3), a stainless steel cylindrical mold with an outer diameter of 21.05 mm and an inner diameter of 19.05 mm, coated with dimethyl silicone oil release agent, is used to cut the mold, resulting in a circular shape with a planar area of ​​90.73 mm². 2 An ion diffusion layer with a thickness of 0.08 mm.

[0065] Example 3

[0066] The rest is the same as in Example 1, except that in step 3), a stainless steel cylindrical mold with an outer diameter of 26.60 mm and an inner diameter of 24.60 mm, coated with dimethyl silicone oil release agent, is used to cut the mold, resulting in a circular shape with a planar area of ​​151.25 mm². 2 An ion diffusion layer with a thickness of 0.08 mm.

[0067] Example 4

[0068] The rest is the same as in Example 1, except that in step 5), 4 mL of the obtained mixture is poured into a mold with a diameter of 15.6 mm to obtain a circular shape with a planar area of ​​60.5 mm². 2 An ion reservoir layer with a thickness of 2 mm.

[0069] Example 5

[0070] The rest is the same as in Example 1, except that in step 3), a 2wt% montmorillonite suspension and a 2wt% gelatin solution are mixed at a volume ratio of 1.5:1, and 12.5 mL of the mixture is filtered to obtain a circular shape with a planar area of ​​121π mm². 2 An ion diffusion layer with a thickness of 0.1 mm.

[0071] Example 6

[0072] The rest is the same as in Example 1, except that in step 5), a 1 wt% sodium alginate solution, a 2 wt% polyvinyl alcohol solution, and a 1 wt% montmorillonite suspension are mixed in a volume ratio of 0.5:1.5:0.5. 4 mL of the resulting mixture is poured into a mold with a diameter of 15.6 mm to obtain a circular shape with a planar area of ​​60.5 mm². 2 An ion reservoir layer with a thickness of 2 mm.

[0073] Example 7

[0074] The remainder is the same as in Example 1, except that in step 1), sodium montmorillonite 1# is used instead of sodium montmorillonite PGW by equal mass; in step 4), sodium alginate E082520 is used instead of sodium alginate E082519 by equal mass; and polyvinyl alcohol A040923 is used instead of polyvinyl alcohol A040928 by equal mass. In step 6), poly(D,L-lactic acid-co-glycolic acid) P875223 is used instead of poly(D,L-lactic acid-co-glycolic acid) P875234 by equal mass.

[0075] Example 8

[0076] 1) A montmorillonite suspension with a solid content of 2wt% was obtained by adding 2kg of sodium montmorillonite PGW to 98kg of water, sonicating at 500W and 40kHz, and stirring at 400rpm for 5h. A montmorillonite suspension with a solid content of 1wt% was obtained by adding 1kg of sodium montmorillonite PGW to 99kg of water, sonicating at 500W and 40kHz, and stirring at 400rpm for 5h.

[0077] 2) Add 1 kg of gelatin E082450 to 99 kg of water and heat to 60°C. Stir at 800 rpm for 20 min to obtain a gelatin solution with a concentration of 1 wt%.

[0078] 3) A 1 wt% montmorillonite suspension and a 2 wt% gelatin solution were mixed at a volume ratio of 1.5:1. The mixture was stirred at 200W power, 40kHz frequency, and 30min for 24h at 400rpm to obtain a homogeneous mixture. 10mL of the mixture was vacuum filtered at 0.08MPa for 1h using a 0.2μm WHATMAN nitrocellulose membrane (purchased from Shanghai Jinpan Biotechnology Co., Ltd.). A 40mm diameter sand filter was used for filtration. The WHATMAN nitrocellulose membrane was peeled off, and the resulting circular filter cake was dried at 30℃ and 40% humidity for 2h. The cake was then molded using a stainless steel cylindrical mold with an outer diameter of 24mm and an inner diameter of 22mm coated with dimethyl silicone oil release agent to obtain a circular shape with a planar area of ​​121πmm². 2 An ion diffusion layer with a thickness of 0.08 mm.

[0079] 4) Add 3 kg of sodium alginate E082519 to 97 kg of water and heat to 60°C. Stir at 400 rpm for 15 min to obtain a sodium alginate solution with a concentration of 3 wt%. Dissolve 4 kg of polyvinyl alcohol A040928 in 96 kg of water and stir at 400 rpm for 5 min to obtain a polyvinyl alcohol solution with a concentration of 4 wt%.

[0080] 5) A 3wt% sodium alginate solution, a 4wt% polyvinyl alcohol solution, and a 2wt% montmorillonite suspension were mixed at a volume ratio of 0.5:1.5:1.5. The mixture was ultrasonically treated for 30 minutes at 200W and 40kHz, and stirred at 800rpm for 12 hours. 5 mL of the resulting mixture was poured into a mold with a diameter of 15.6 mm. The mixture was pre-frozen at -45℃ for 2 hours, and then freeze-dried at -20℃ and 20Pa for 24 hours to obtain an aerogel. The freeze-dried aerogel was immersed in a 30mmol / L calcium chloride aqueous solution at a mass-to-volume ratio of 1 g:5 mL for 5 minutes, filtered, and washed once with water to obtain an ion-crosslinked aerogel. The ion-crosslinked aerogel was immersed in a 100mmol / L calcium chloride aqueous solution at a mass-to-volume ratio of 1 g:5 mL for 24 hours, filtered, and the surface moisture was absorbed with filter paper to obtain a circular aerogel with a planar area of ​​60.5π mm². 2 An ion storage and release layer with a thickness of 3 mm.

[0081] 6) Add 3 kg of poly(D,L-lactic acid-co-glycolic acid) P875234 to 97 kg of ethyl acetate and stir at 500 rpm for 30 min until completely dissolved to obtain a poly(D,L-lactic acid-co-glycolic acid) solution with a concentration of 3 wt%.

[0082] 7) The ion diffusion layer is laid flat on the surface of the glass, and the ion storage and release layer is laid flat on the surface of the ion diffusion layer so that the geometric centers of the two coincide. A 3wt% poly(D,L-lactic acid-co-glycolic acid) solution is applied once, and then the mixture is cured at 25°C and 0.03MPa vacuum for 30 minutes to obtain a montmorillonite-based biomimetic bone repair composite material with an encapsulation layer thickness of 0.1mm.

[0083] Comparative Example 1

[0084] 1) A montmorillonite suspension with a solid content of 2wt% was obtained by adding 2kg of sodium montmorillonite PGW to 98kg of water, sonicating at 500W and 40kHz, and stirring at 400rpm for 5h. A montmorillonite suspension with a solid content of 1wt% was obtained by adding 1kg of sodium montmorillonite PGW to 99kg of water, sonicating at 500W and 40kHz, and stirring at 400rpm for 5h.

[0085] 2) Add 2 kg of gelatin E080142 to 98 kg of water and heat to 60°C. Stir at 800 rpm for 20 min to obtain a gelatin solution with a concentration of 2 wt%.

[0086] 3) A montmorillonite suspension with a solid content of 2wt% and a gelatin solution with a concentration of 2wt% were mixed at a volume ratio of 1:1. The mixture was stirred at a power of 200W, a frequency of 40kHz, an ultrasonic time of 30min, and a speed of 400rpm for 24h to obtain a homogeneous mixture. 10mL of the mixture was vacuum filtered for 1h under a vacuum of 0.08MPa. The filtration was performed using a WHATMAN nitrocellulose membrane with a pore size of 0.2μm (purchased from Shanghai Jinpan Biotechnology Co., Ltd.) and a sand core filter with a diameter of 40mm. The WHATMAN nitrocellulose membrane was peeled off to obtain a circular filter cake. The cake was dried at 30℃ and 40% humidity for 2h. The cake was then molded using a stainless steel cylindrical mold with an outer diameter of 24mm and an inner diameter of 22mm coated with dimethyl silicone oil release agent to obtain an ion diffusion layer with a circular shape, a planar area of ​​121πmm2, and a thickness of 0.08mm.

[0087] 4) Add 1 kg of sodium alginate E082519 to 99 kg of water and heat to 60°C. Stir at 400 rpm for 15 min to obtain a sodium alginate solution with a concentration of 1 wt%. Dissolve 2 kg of polyvinyl alcohol A040928 in 98 kg of water and stir at 400 rpm for 5 min to obtain a polyvinyl alcohol solution with a concentration of 2 wt%.

[0088] 5) Mix a 1 wt% sodium alginate solution, a 2 wt% polyvinyl alcohol solution, and a 1 wt% montmorillonite suspension at a volume ratio of 1:1:1, and sonicate at 200W power, 40kHz frequency for 30 minutes, with a rotation speed of 800 rpm. Stir at rpm for 12 hours, pour 6 mL of the resulting mixture into a mold with a diameter of 15.6 mm, pre-freeze at -45℃ for 2 hours, and then freeze-dry at -20℃ and 20 Pa for 24 hours to obtain an aerogel. Immerse the freeze-dried aerogel in a 50 mmol / L calcium chloride aqueous solution at a mass-to-volume ratio of 1 g: 10 mL for 5 minutes, filter and separate, wash once with water to obtain an ion-crosslinked aerogel. Immerse the ion-crosslinked aerogel in a 200 mmol / L magnesium chloride aqueous solution at a mass-to-volume ratio of 1 g: 10 mL for 12 hours, then filter and separate, absorb the surface moisture with filter paper to obtain an ion storage layer with a circular shape, a planar area of ​​60.5 mm2, and a thickness of 3 mm.

[0089] 6) Add 6 kg of polylactic acid P729201 to 94 kg of ethyl acetate and stir at 500 rpm for 30 min until completely dissolved to obtain a polylactic acid solution with a concentration of 6 wt%.

[0090] 7) The ion diffusion layer is laid flat on the surface of the glass, and the ion storage and release layer is laid flat on the surface of the ion diffusion layer so that the geometric centers of the two coincide. A 6wt% polylactic acid solution is applied three times, with a time interval of 10 min between two consecutive applications. Then it is placed at 25℃ and a vacuum degree of 0.03MPa for 30 min to cure, resulting in a montmorillonite-based biomimetic bone repair composite material with an encapsulation layer thickness of 0.3 mm.

[0091] The bone repair composite materials prepared in the above embodiments and comparative examples were subjected to the following performance tests:

[0092] 1. Electrical Performance Testing: Ion current was measured using a Keithley 2612B digital source meter. First, a montmorillonite-based biomimetic bone repair composite material prepared in one example or comparative example was placed on the surface of 20 mL of phosphate buffered saline (PBS), ensuring full contact between the ion diffusion layer at the bottom of the material and the PBS solution, while the encapsulation layer remained exposed to air. Then, the test circuit was connected, with one electrode directly inserted into the ion reservoir layer inside the composite material and connected to the positive terminal of the digital source meter; the other electrode was inserted into the PBS solution and connected to the negative terminal of the digital source meter. During the test, the digital source meter was set to zero bias (0 V) mode, and the spontaneous ion current of the bone repair system was continuously monitored in real time without any applied voltage for a test period of 26 days. As ions were gradually released from the ion reservoir layer, the change in ion current over time was recorded in real time to obtain a complete ion current-time (IT) curve, and the maximum achievable current value and the duration (day) of current exceeding 1 μA were recorded.

[0093] Phosphate buffer solution (PBS, pH=7.4) consists of NaCl (137 mM), KCl (2.7 mM), Na2HPO4 (8.1 mM) and KH2PO4 (1.47 mM) and is used to simulate the body fluid environment.

[0094] 2. ICP-MS: The montmorillonite-based biomimetic bone repair composite material prepared in one example or comparative example was placed on the surface of 20 mL of phosphate buffered saline (PBS), and the concentration changes of released ions from the composite material were monitored. 2 mL of PBS solution was collected every 1 day. Inductively coupled plasma mass spectrometry (ICP-MS) was used to analyze the Mg content. 2+ or Ca 2+ Quantitative analysis of Mg concentration was performed. This was achieved by analyzing the concentration of Mg in PBS at different time points. 2+ or Ca 2+ The concentration was determined, and the ion release behavior of the composite material was obtained as a function of time. The concentration of Mg in the PBS solution was also recorded at 26 days. 2+ or Ca 2+ Ion concentration.

[0095] Table 1 Performance Test Results

[0096]

[0097] From Table 1 and Figure 3 As can be seen, the concentration of Mg in the PBS solution reached 808-1130 μM after 26 days of ICP-MS testing, especially in Example 1. 2+ or Ca 2+ The ion concentration reached 1.13 mM after 26 days, which was higher than that of plasma Mg.2+ or Ca 2+ The concentration (approximately 0.7 mM) falls within the osteogenic activity window (1-5 mM), meeting the concentration requirements for triggering the proliferation, migration, and early osteogenic differentiation of bone marrow mesenchymal stem cells and osteoblasts.

[0098] Furthermore, the maximum spontaneous ion current of the composite materials in each embodiment of the present invention can reach 1.69-2.48 μA, and can maintain an effective ion current of more than 1 μA for 18.4-22 days. This current range matches the effective micro-electrical stimulation window for bone repair, and can provide a suitable electrical microenvironment for the proliferation and differentiation of osteoblast-related cells. Combined with the analysis of ICP-MS ion concentration results, it can be seen that the higher the total amount of metal ions released by the system, the greater the ion concentration gradient that can be provided, the higher the corresponding peak ion current, and the longer the maintenance period of the long-term electrical signal.

[0099] The above results demonstrate that the directional diffusion layer, ion storage and release layer, and sealing encapsulation layer of this invention work synergistically: on the one hand, they can sustainably release magnesium / calcium metal ions at concentrations within the bone-promoting range; on the other hand, they rely on the directional ion transport channel and the leak-proof encapsulation structure to form a long-term stable endogenous ion flow, continuously outputting micro-electrical signals adapted to the needs of bone regeneration. The results of Comparative Example 1 show that only suitable encapsulation layer materials can ensure that ions do not diffuse and leak randomly, guarantee the material's metal ion release capability, and achieve long-term stable micro-electrical signal output.

[0100] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

Claims

1. A biomimetic bone repair composite material based on montmorillonite, characterized in that, The montmorillonite-based biomimetic bone repair composite material is composed of an ion diffusion layer, an ion storage and release layer, and an encapsulation layer. The ion diffusion layer and the ion storage and release layer have the same planar shape and are tightly bonded together to form an integrated biphase structure. The encapsulation layer completely covers the integrated biphase structure, leaving the surface of the ion diffusion layer away from the ion storage and release layer unencapsulated. The ion diffusion layer is prepared by self-assembly of montmorillonite and gelatin in water followed by vacuum filtration. The ion storage and release layer is prepared by self-assembly of sodium alginate, polyvinyl alcohol, and montmorillonite in water followed by freeze-drying to form a porous aerogel, which is then further processed using Ca... 2+ The encapsulation layer is prepared by cross-linking and loading divalent metal ions; the encapsulation layer is prepared by curing poly(D,L-lactic acid-co-glycolic acid) solution; the planar area ratio of the ion diffusion layer and the ion storage and release layer is 1.5-2.5:

1.

2. The montmorillonite-based biomimetic bone repair composite material according to claim 1, characterized in that, The planar area ratio of the ion diffusion layer to the ion storage and release layer is 1.5-2:1; the thickness of the ion diffusion layer is 0.02-0.1 mm, preferably 0.08-0.1 mm; the thickness of the ion storage and release layer is 2-5 mm, preferably 2-3 mm; and the thickness of the encapsulation layer is 0.1-0.3 mm.

3. The montmorillonite-based biomimetic bone repair composite material according to claim 1, characterized in that, The divalent metal ions are selected from at least one of calcium ions and magnesium ions; the self-assembly conditions are: first ultrasonic treatment, then stirring.

4. The montmorillonite-based biomimetic bone repair composite material according to claim 1, characterized in that, The montmorillonite is fed in the form of a montmorillonite suspension, and the gelatin is fed in the form of a gelatin solution; the solid content of the montmorillonite suspension is 1-2 wt%; the concentration of the gelatin solution is 1-2 wt%; and the volume ratio of the montmorillonite suspension to the gelatin solution is 1-1.5:

1.

5. The montmorillonite-based biomimetic bone repair composite material according to claim 1, characterized in that, The montmorillonite is sodium-based montmorillonite with an average particle size of 10-70µm and an ion exchange capacity of 90-145meq / 100g; the gelatin has a glue strength of 200-300gBloom.

6. The montmorillonite-based biomimetic bone repair composite material according to claim 1, characterized in that, The sodium alginate is added in the form of a sodium alginate solution, the polyvinyl alcohol is added in the form of a polyvinyl alcohol solution, and the montmorillonite is added in the form of a montmorillonite suspension; the concentration of the sodium alginate solution is 1-3%, the concentration of the polyvinyl alcohol solution is 2-4 wt%, and the solid content of the montmorillonite suspension is 1-2 wt%, with a volume ratio of 0.5-1.5:0.5-1.5:0.5-1.

5.

7. The montmorillonite-based biomimetic bone repair composite material according to claim 1, characterized in that, The viscosity of the sodium alginate is 100-400 mPa·s; the weight-average molecular weight of the polyvinyl alcohol is 80,000-120,000.

8. The montmorillonite-based biomimetic bone repair composite material according to claim 1, characterized in that, The concentration of the poly(D,L-lactic acid-co-glycolic acid) solution is 3-6 wt%; the weight average molecular weight of the poly(D,L-lactic acid-co-glycolic acid) is 20,000-60,000, and the molar ratio of lactide to glycolide is 50-85:15-50.

9. The method for preparing the montmorillonite-based biomimetic bone repair composite material according to any one of claims 1-8, characterized in that, Includes the following steps: S1 ion diffusion layer: Montmorillonite, gelatin and water are mixed to form a liquid phase, which is then self-assembled, vacuum filtered and dried for later use; S2 ion storage layer: Sodium alginate, polyvinyl alcohol, montmorillonite, and water are mixed to form a liquid phase for self-assembly, poured into a mold, and freeze-dried to obtain an aerogel. Ca 2+ Cross-linked and loaded with divalent metal ions, ready for use; S3 Bionic Bone Repair Composite Material Based on Montmorillonite: An ion diffusion layer is laid flat on a planar glass surface, an ion storage and release layer is laid flat on the surface of the ion diffusion layer to form an integrated biphase structure, a poly(D,L-lactic acid-co-glycolic acid) solution is applied, and then cured.

10. The application of the montmorillonite-based biphasic biomimetic bone repair composite material according to any one of claims 1-8 as a dental repair material or a craniofacial bone repair material.

Citation Information

Patent Citations

  • A piezoelectric active bone repair composite material and its preparation method

    CN104208754B

  • A 3D printed piezoelectric bone repair scaffold based on shape memory polymer and its preparation method

    CN116328043B

  • Hydrogel for promoting cartilage repair by piezoelectric effect, preparation method and application thereof

    CN116942922B